PERUBAHAN SOSIAL DAN TRADISI PHUBBING: TELAAH PERILAKU KOMUNIKASI MASYARAKAT DIGITAL DI KELURAHAN SURYAWANGI, LOMBOK TIMUR - Ihsan, Hamzani Khairul; Ferdiansyah, Daeng Sani; Yani, Muhammad (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2021)
The presence of new media such as gadgets became a staple of digital society, namely the generation that grew up in the 20th century. One of the dmpak produced by digitalization is the tradition of phubbing, which is the condition of society that prioritizes gadgets over friends around. Phubbing occurs because users are unable to utilize technology wisely as a result of feeling bored and conversations that are no longer interesting. The research method used is qualitative with a type of phenomenology. The results showed that phubbing one of the behaviors that are contrary to social norms that exist in public life one of them is mutual respect between each other and communication. The attitude of dependence on gadgets makes the digital community in Suryawangi become an introverted human being to his own world.